Magnetic iron oxide nanoparticles functionalized with C60 phosphonic acid derivative for catalytic reduction of 4-nitrophenol. Issue 3 (June 2019) - Piotrowski, Piotr; Krogul-Sobczak, Agnieszka; Kaim, Andrzej
Graphical abstract: Abstract: Synthesis and self-assembly of C60 fullerene phosphonic acid derivative onto magnetic iron oxide nanoparticles stabilized with oleic acid (OA) for catalytic applications is presented. The as obtained composite nanoparticles were characterized using transmission electron microscopy (TEM), dynamic light scattering (DLS), X-ray photoelectron spectroscopy (XPS), thermogravimetric analysis (TGA) and cyclic voltammetry (CV). As result, introduction of functionalized fullerenes onto surface of magnetic nanoparticles was confirmed. Proposed deposition procedure and use of phosphonic acid anchoring group resulted in high fullerene content in the composite material with approximately 2.6:1 OA to C60 ratio. Afterwards efficient utilization of resulting catalyst in the reduction of 4-nitrophenol using sodium borohydride in water is reported and the kinetics of the reaction have been evaluated. Resulting rate constant was found to be k = 1.54·10 −3 ·s −1 . Moreover, magnetic properties of the engineered catalyst allow its simple removal by using external magnetic field and reuse without noticeable loss of efficiency. Presented catalytic nanoparticles may be used not only for synthesis of aromatic amines but also can find application for decontamination of water polluted by 4-nitrophenol.